2016
DOI: 10.1108/scm-07-2015-0278
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of reverse exchange systems used for medical devices in the UK National Health Service (NHS)

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
(82 reference statements)
0
14
0
2
Order By: Relevance
“…A study of the reverse exchanges in healthcare sector is discussed by Xie et al (2015). Through case study analysis and comparison their work aims to investigate the scale and use of Information Communication Technology (ICT) in managing medical devices in the National Health Service (NHS), with a focus on Reverse Exchange (RE) systems.…”
Section: Introduction To Special Issue Papersmentioning
confidence: 99%
“…A study of the reverse exchanges in healthcare sector is discussed by Xie et al (2015). Through case study analysis and comparison their work aims to investigate the scale and use of Information Communication Technology (ICT) in managing medical devices in the National Health Service (NHS), with a focus on Reverse Exchange (RE) systems.…”
Section: Introduction To Special Issue Papersmentioning
confidence: 99%
“…Similarly, whether to implement a technology is up to each hospital to decide and may differ depending on the focus areas of the hospital (Xie et al, 2016).…”
Section: Factors Impacting Technology Adoption In Hospital Bed Logistmentioning
confidence: 99%
“…DiscussionThe benefits realized from a technology differ between companies(Xie et al, 2016); what is right for one company may not be right for others. The state of a process and the…”
mentioning
confidence: 99%
“…Remanufacturing as part of RE lacks practical research and Junior and Filho (2012) found mostly theoretical studies in their review of the literature. Xie et al (2016) and Breen, Xie and Cherrett (2016) have the most pioneering papers on RE of medical devices so far with a limited number of other studies for specific types of equipment such as wheelchairs (Chouinard et al, 2009).…”
Section: Reverse Exchangementioning
confidence: 99%